A review of heat issues in underground metalliferous mines - T. Payne (Society for Mining, Metallurgy & Exploration, 2009)
Underground heat issues are mainly focused on the detrimental effects to a workers health. However, working in hot, humid conditions has other negative effects. Studies have shown that safety, productivity, workforce morale and operating cost are also worsened in these conditions. The human body has several mechanisms for rejecting heat and remaining cool. However, once the air temperature exceeds about 34°C, the only effective mechanism is by evaporation of sweat from the skin. This is assisted by acclimatisation which is the human body?s enhanced ability to combat extended exposure to heat. The body has to remain well hydrated when working in heat as even small degrees of dehydration cause significant decreases in the ability to work in heat. There are two ways in which heat load can be reduced: Through use of refrigeration/vent/cooling to reduce thermal stress on workers; Reduce the contribution that heat sources have to underground heat load (e.g. reduce idle time, fleet size, etc). Some of the sources of underground heat have the potential to be more manageable than others. Geothermal heat and heat from autocompression will be found in all mining situations in varying degrees depending on geothermal gradient and surface temperature, however, the use of equipment and blasting may be streamlined to reduce the underground heat load. It is through a combination of the available options that most mines will successfully control their heat related problems. Mt Isa, which has been a focus for heat related study in Australia, has successfully implemented protocols for working in heat. Through combining these with the installation of a surface bulk air cooling plant, Mt Isa has consistently reduced the incidence of heat illness. This is likely to be the most cost effective method of reducing heat load for deep mines in Australia. Shallower mines which may only occasionally encounter hot conditions should consider more portable cooling options. This study will review the heat issues in underground Australian metalliferous mines.